Relationship between stressors and health among IIUM academics : assessing distress and eustress and mediating variabless - Kiran, Madeeha (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
This research examined the relationships between stressors, eustress/distress and health by testing four hypotheses about the direction of the relationships between the variables and possible mediation by eustress/distress. The variables were measured by administering self report questionnaires to the target sample of IIUM academics (N-125). The results from correlation analysis indicated that there were significant positive relationships between all stressors and negative affect and there was also a significant negative relationship between negative affect and health, r=-0.252, n=125, p=0.01, two tail. With regard to the relationships between stressors and eustress, the coefficients showed that there was a negative relationship between the two sets of variables as expected but the relationships did not reach significance. The positive relationship between eustress and health did, however, reach significance, r=0.248, n=125, p=0.01, two tailed. Lastly, the results from a series of hierarchical regressions showed that only the relationship between Student Interaction (stressor) and health was fully mediated by distress. The study highlights the importance of studying both the eustress and distress responses to stressors and the impact of these responses on health. The findings also have significance for the way in which universities may attempt to improve the health of their academics by distress prevention and eustress generation.